The Impact of Service Quality and Word of Mouth on Purchase Decision on MSMEs - Octaviana Arisinta; Ulum, Romiftahul (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2023)
The challenge of MSMEs to survive after Covid-19 is increasingly hard. Industry 4.0 has been taking over several jobs of human being. Even though, the MSMEs that survive and develop their business and adapt with technology and online platform is able to gain the attention of customer. The online platform for selling a product or service is currently in high demand due to ease of use and ease of payment. Therefore, company should provide best quality product, best service quality, and catchy promotion to gain the attention of consumer or customer. Moreover, there are few of study that investigate the WOM and service quality on purchase intention since service quality is investigating customer satisfaction in common while WOM is directly investigate it relationship with purchase intention. Therefore, this study is aimed to investigate the relationship of service quality and word of mouth on purchase decision partially and simultaneously. The method employs in this study is quantitative method with multiple regression analysis. The data of this study is primary data which obtained from the respondents directly through questionnaire. The result of this study partially, service quality has a positive significant relationship on purchase decision as well as WOM has a positive significant relationship on purchase decision. Meanwhile, simultaneously, service quality and WOM has a positive significant impact on purchase decision with level of relationship about 54.6%.